Pengaruh Kepemimpinan Instruksional Kepala Sekolah Terhadap Kinerja Mengajar Guru SMK Se-Kecamatan Bojongloa Kidul Kota Bandung - Hidayat, Shandy Nugraha; Herawan, Endang; Prihatin, Eka (Jurnal ADPEND, 2016)
Research is called âThe Influence of Principal Instructional Leadership to the TeachingÂ Performance of Vocational Secondary School Teacher at Bojongloa Kidul BandungÂ City.âThis research using two variable, x variable is Principal Instructional LeadershipÂ and y variable is Teaching Performance. The study is done in 6 Vocational SecondaryÂ schools at Bojongloa Kidul Bandung with respondents research the school teacher inÂ each school. In general the purpose of this research was to give how much influence ofÂ Principal Instructional Leadership to the Teaching Performance of VocationalÂ Secondary School Teacher at Bojongloa Kidul Bandung City. The study is done by usingÂ the method descriptive and approach quantitative supported to the study literature.Â Technique data collection using a questionnaire, who became population is a teacher ofÂ vocational secondary school at Bojongloa Kidul Bandung City with a sample of 70Â respondents. Analysis thinks in this study use some help program Microsoft Excel 2007Â and application spss 21.0 for windows. The calculation on Weight Means Score (WMS),Â shows that Principal Instructional Leadership Vocational Secondary School Teacher atÂ Bojongloa Kidul Bandung City be in the very high with an average all the aspects 4,38.Â For the performance of teachers to teach are in the high with an average all the aspectsÂ 4,31. Based on the calculation t test obtained thitung = 20.58> ttabel = 1.668 means thatÂ there is a very significant influence between Instructional Leadership Principal TeacherÂ Teaching Performance Against SMK Bojongloa District of Bandung Kidul, byÂ calculating the coefficient of determination stating their influence between the variablesÂ of 84.64%.